Low Voltage Ride-through Capability Enhancement of Doubly Fed Induction Generator Based Wind Turbines under Voltage Dips - Youness Boukhris; Aboubakr El Makrini; Hassan El Moussaoui; Hassane El Markhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Based on the advantages of doubly fed induction generator (DFIG)-based wind turbine (WT). This paper proposes a new control strategy to improve the ride-through capability of DFIG-based WTs in the event of a grid fault. The proposed method is performed by using the DFIG converters control and the addition of the damping resistances connected to the DC circuit, to follow the requirements defined by the grid codes. The proposed ride-through solution limits the peak values of the DC link voltage, the rotor inrush current, electromagnetic torque and DFIG transient response at the times of occurrence and clearing the fault. The proposed solution is simulated and compared with the crowbar solution using MATLAB/Simulink environment.